PS3:54 Characteristic features of haematological involvement and its effect on damage accrual in patients with systemic lupus erythematousus: preliminary results from a multicenter european cohort. (21st March 2018) - Yavuz, S; Cansu, D; Crisafulli, F; Antunes, AM; Nikolopoulos, D; Tascilar, K; Korkmaz, C; Andreoli, L; Moraes-Fontes, F; Tincani, A; Bertsias, G
Abstract : Background and aim: We studied haematological manifestations (HM) and their impact on the progression of damage in systemic lupus erythematosus (SLE) using a multicenter European cohort of patients. Methods: We examined the observational data of a SLE patients with serial clinical and laboratory measurements of every 6 months for 2 years gathered from 4 different countries. Each collaborative centre was asked for a contribution of fifty or more consecutive SLE patients. We compared clinical features, antibody profiles, SLEDAI-2K and SDI in patients with and without HM using Chi-Square and Student's t-tests for categorical and continuous variables, respectively. Multivariate Cox Proportional hazards regression was used the investigate the quartiles of leukocytes, lymphocytes and platelets at every time point (at 0, 6, 12, 18, 24 months) in relation to the damage characterised by the SDI scores. Probability of change in damage index (from SDI=0 to SDI equal or greater than 1) was calculated using mixed models logistic regression. Adjustments ma Results are presented as odds ratios (ORs) with their 95% CIs; results were defined significant as a p 0.05. Results: So far, 751 measurements of 159 patients were examined. Mean age was 44.9 (13.5) vs 44.0 (12.9) for patients with and without HM, respectively (p=NS). Mean disease duration at the time of cohort created was 11.1 (6.2) vs 10.8 (4.9) in patients with or without HM. Demographic features, clinical characteristics of patients with HM at SLE diagnosis or during the follow up are demonstrated in table 1. Sex, ethnicity and baseline autoantibodies showed no influence on damage. SLEDAI-2K was associated with an increased OR of 2.1 [95% CI: 1.29 to 3.42] for damage. Conclusion: Preliminary results imply that disease activity predicts future damage accrual in patients with haematological manifestations.